Bioevents correlation of planktic foraminifers and radiolarians from the Cenomanian to Turonian, southeastern Mexico - Ornelas-Sánchez, María; Navarrete, S. Franco; Martinez, M. Granados (Anuário do Instituto de Geociências, 2006)
Abstract